Discussion of “unsaturated hydraulic conductivity of two compacted barrier soils” - Leong, Eng Choon (2011)
Unsaturated hydraulic conductivities were measured in the laboratory and the field for two compacted fine-grained soils used as barrier layers in landfill final covers. The instantaneous profile method was used for the laboratory and field measurements. Results of the tests show that similar unsaturated hydraulic conductivities exist in the laboratory and field for both soils. Furthermore, results of laboratory tests conducted with specimens prepared at different molding water contents and compactive efforts show that the unsaturated hydraulic conductivity function is insensitive to molding water content for matric suctions exceeding 20 m, but is strongly affected by compactive effort. Specimens compacted with modified Proctor effort had unsaturated hydraulic conductivities approximately one order of magnitude lower than those compared with a standard Proctor effort. It is also shown that estimated unsaturated hydraulic functions based on parameters describing the soil-water characteristic curve underpredict the unsaturated hydraulic conductivity functions of these barrier soils.